Proteomic analysis of the Trypanosoma cruzi ribosomal proteins - Juri Ayub, Maximiliano (2009)
Trypanosoma cruzi is a parasite responsible for Chagas disease. The identification of new targets for chemotherapy is a major challenge for the control of this disease. Several lines of evidences suggest that the translational system in trypanosomatids show important differences compared to other eukaryotes. However, there little is known information about this. We have performed a detailed data mining search for ribosomal protein genes in T. cruzi genome data base combined with mass spectrometry analysis of purified T. cruzi ribosomes. Our results show that T. cruzi ribosomal proteins have ∼50% sequence identity to yeast ones. Nevertheless, some parasite proteins are longer due to the presence of several N- or C-terminal extensions, which are exclusive of trypanosomatids. In particular, L19 and S21 show C-terminal extensions of 168 and 164 amino acids, respectively. In addition, we detected two 60S subunit proteins that had not been previously detected in the T. cruzi total proteome; namely, L22 and L42.